A Huge Fetal Sacrococcygeal Teratoma with a Vascular Disruption Sequence. (1st August 2015) - Atis, Alev; Kaya, Basak; Acar, Deniz; Polat, Ibrahim; Gezdirici, Alper; Gedikbasi, Ali
<x xml:space="preserve">Abstract</x> Fetal sacrococcygeal teratomas (SCTs) occur in one to two per 20 000 pregnancies that cause high-output cardiac failure. High-output cardiac failure leads to polyhydramnios, hydrops, intrauterine fetal demise and preterm birth. Vascular disruption defects refer to those involving the interruption or destruction of some part of the fetal vasculature. We present a rare case of huge SCT causing multiple fetal disruption defects like cleft lip and palate and limb anomalies besides hydrops.